British counterterrorism, the international prohibition of torture, and the multiple streams framework - Heaphy, Janina (Policy and Politics, 2022)
After years of violating the basic principles of human rights in the name of counterterrorism, western democracies have begun to implement extraterritorial safeguards that extend protections under the Convention against Torture to foreigners abroad. The case of the UK and the development of the ‘Principles’ in 2019, however, presents a particular puzzle to policymaking research, as it challenges traditional hypotheses regarding the opening of problem windows within the multiple streams framework. Accordingly, the UK presents an interesting case in which a powerful state willingly engaged in self-restraint, despite little electoral pressure to do so and a persistently high terrorist threat. Drawing on theory-building process-tracing, this article addresses this gap using data from semi-structured interviews with British policy experts to present a refined hypothesis, which can also be applied to policy fields of little public interest and processes of foreign policymaking
Created from Fastlane, Scopus look-up
Keywords: Convention against torture; Counterterrorism; Foreign policy; Human rights; Multiple streams framework; Uk